Validation of the process criteria for assessment of a hospital nursing service - Liliane Bauer Feldman; Isabel Cristina Kowal Olm Cunha; Maria D'Innocenzo (Universidade de São Paulo, 2013)
OBJECTIVE: to validate an instrument containing process criteria for assessment of a hospital nursing service based on the National Accreditation Organization program. METHOD: a descriptive, quantitative methodological study performed in stages. An instrument constructed with 69 process criteria was assessed by 49 nurses from accredited hospitals in 2009, according to a Likert scale, and validated by 16 judges through Delphi rounds in 2010. RESULT: the original instrument assessed by nurses with 69 process criteria was judged by the degree of importance, and changed to 39 criteria. In the first Delphi round, the 39 criteria reached consensus among the 19 judges, with a medium reliability by Cronbach's alpha. In the second round, 40 converging criteria were validated by 16 judges, with high reliability. The criteria addressed management, costs, teaching, education, indicators, protocols, human resources, communication, among others. CONCLUSION: the 40 process criteria formed a validated instrument to assess the hospital nursing service which, when measured, can better direct interventions by nurses in reaching and strengthening outcomes.